Employee performance: The role of competence, organizational culture, and motivation - Ridwan, Selvy Amelia; Yusuf, Muhammad; Marhumi, Sitti (Journal of Management and Business Insight, 2023)
Purpose-A company's internal and external elements might affect employee performance. This study focuses on how motivation, organizational culture, and competence influence employee performance. Design/Methodology/Approach- The study population consisted of all employees at PT. Telkon Indonesia Regional VII.  Data for this study was collected through questionnaires and 54 respondents were collected. The data analysis of this study was processed using the SPSS 25 statistical tool. Findings-The findings showed that PT. Telkom Indonesia Regional VII employees' performance is positively impacted by competency and organizational culture. However, motivation shows the opposite effect on PT. Telkom Indonesia Regional VII employees' performance. These findings suggest that encouraging a positive company culture and increasing staff competency can both enhance employee performance. However, motivation had an insignificant effect on increasing employee performance in this study. Research limitations/implications-For every company, it should be necessary to improve or optimize competence, work culture, and motivation in order to encourage morale which ultimately affects employee performance. This finding shows that improving employee performance can be done in various ways including internal and external aspects of the company. Originality/value-Study of employee performance in service business, especially PT. Telkom Indonesia Regional VII is still quite limited. Previous research similar to this study in measuring employee performance using different indicators and different objects.